Quotation, Revision, and Narrative Structure in Giraldus Cambrensis’s Itinerarium Kambriae - Henley, Georgia (The Journal of Medieval Latin, 2014)
Abstract Giraldus Cambrensis is renowned for his historical and ethnographic works on Ireland and Wales. His sources for these texts are less clear, and the purpose of this article is to examine his usage of classical, biblical, and patristic texts as sources for quotations in the Itinerarium Kambriae, with reference to his other works when necessary. It argues that the quotations which appear in the text as altered from the original source are not the result of misquotation or faulty memory, as has been claimed previously, but of deliberate reworking to fit the context and the argument of the passage in which the quotation appears. This deft manipulation of quotations to support his argument reveals a level of rhetorical skill and awareness not previously acknowledged. The article also finds attribution for several quotations whose origins were previously unknown. As Giraldus was in the habit of adding quotations and self-quoted passages to his works over time, this discussion is followed by an examination of his revisions to the Itinerarium Kambriae and the implications of these revisions on the transmission of his work. Abstract Giraldus Cambrensis est connu pour ses ecrits historiques et ethnographiques sur l’Irlande et le Pays de Galles. Ses sources pour ces textes sont moins claires, et le but de cet article est d’examiner son usage des textes classiques, bibliques et patristiques comme sources de citations dans l’Itinerarium Kambriae, en référant à ses autres oeuvres quand il en est nécessaire. L’article soutient que les citations qui figurent dans le texte ne sont pas modifiées de ses sources d’origine à cause d’une citation erronée ou d’une mémoire défaillante, comme l’on avait auparavant soutenu, mais d’un remaniement délibéré pour les adapter au contexte et à l’argument du passage dans lequel la citation figure. Cette manipulation habile des citations pour soutenir son argument révèle un niveau de compétence et de conscience rhétoriques ignoré jusqu’à présent. L’article trouve aussi les attributions de plusieurs citations dont les sources étaient auparavant inconnues. Puisque Giraldus a l’habitude d’ajouter des citations et des passages de ses propres œuvres à ses écrits au cours du temps, cette discussion est suivie par une étude de ses révisions de l’Itinerarium Kambriae et les conséquences de ces révisions sur la transmission de son œuvre. (Translation by Gregory Darwin)